1997
DOI: 10.1152/jappl.1997.83.3.927
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in growth and body composition during puberty. I. Comparing multicompartment body composition models

Abstract: A four-compartment (4C) model of body composition was used as a criterion to determine the accuracy of three-compartment (3C) and two-compartment (2C) models to estimate percent body fat (%BF) in prepubertal and pubertal boys (genital I & II, n = 17; genital III & IV, n = 7) and girls (breast I & II, n = 8; breast III & IV, n = 15). The 3C water-density (3C-H2O) and 3C mineral-density models, dual-energy X-ray absorptiometry, the Lohman age-adjusted equations, the Slaughter et al. skinfold equations, and the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
80
3
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 13 publications
11
80
3
1
Order By: Relevance
“…Thus some of the upper limb fat mass may have been left out in the calculation of fat mass by the computer software. To our knowledge, this is the first study to crossvalidate the DXA against the 4C model in children using the Lunar DPX-L. Roemmich et al (20) found similar results using a Hologic DXA. That study found percent fat estimates by DXA to be systematically 3 1.0332 Ϯ 0.0204 Body density from HW, g/cm 3 1.0384 Ϯ 0.0187* TBW kg 25.9 Ϯ 6.9…”
Section: Dxa Findingssupporting
confidence: 57%
See 1 more Smart Citation
“…Thus some of the upper limb fat mass may have been left out in the calculation of fat mass by the computer software. To our knowledge, this is the first study to crossvalidate the DXA against the 4C model in children using the Lunar DPX-L. Roemmich et al (20) found similar results using a Hologic DXA. That study found percent fat estimates by DXA to be systematically 3 1.0332 Ϯ 0.0204 Body density from HW, g/cm 3 1.0384 Ϯ 0.0187* TBW kg 25.9 Ϯ 6.9…”
Section: Dxa Findingssupporting
confidence: 57%
“…1) To correct for isotope exchange with nonaqueous hydrogen atoms, we used a correction of 1.04, whereas others used a smaller correction (0.95-0.97), thus reducing our estimates of TBW by ϳ6% (1, 13, 14). 2) Children in our group were substantially heavier and more obese than those in the studies of Hewitt et al and Roemmich et al (13,20). This could potentially lead to more variation in the estimates of TBW.…”
Section: Tbw Findingsmentioning
confidence: 62%
“…In a group of prepubertal children, the Slaughter formulas were moderately effective, explaining only 69% of the variance in the DXA fat mass, 28 and in a group of 47 10-13-y-old children the Slaughter formula was significantly better (r ¼ 0.79) than other skinfold equations in predicting %BF when compared to DXA. 29 In the present population of healthy adolescents, estimates of body fatness utilizing the Slaughter formulas were significantly correlated with DXA measurements. From the previous data and from the present study it can be concluded that measures of fatness derived from the Slaughter formulas provide adequate information for purposes of ranking individual degrees of adiposity within a population.…”
Section: Discussionmentioning
confidence: 60%
“…First, DXA estimates of body composition are known to be influenced by the higher degree of soft tissue hydration in younger children. 29,32 Second, there would likely be substantial differences in total body fat in an older cohort, since body size changes significantly with pubertal development. Similarly, the relations between measures of body fatness were not significantly different in short compared to tall children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation